Systemic, Sectoral Risk and the Myth of a Corporate Savings Glut - Dadam, Vincent; Viegi, Nicola (World Bank, Washington, DC, 2018)
This note investigates the nature of corporate savings in South Africa. The first part focuses on the empirical impact of uncertainty on investment in the manufacturing sector, while the second part discusses factors influencing corporate cash hoarding and assesses whether South African firms’ behavior is peculiar. The results show that sectoral and systemic risks – our measures of uncertainty – consistently impede investment in the South African manufacturing sector, which could explain in part for firms increasing their savings. Further reasons for that behavior include precautionary measures when economic conditions are unfavorable, increasing appetite for investment abroad at the expense of domestic investment, cash provision for amortization purposes and balance sheet management.